A Dosing-Spoon-Based Electrochemical Sensor for Fast Assessment of Andrographis paniculata Extracts. Issue 5 (1st May 2022) - Sangsawang, Rachanon; Thavarungku, Panote; Kanatharana, Proespichaya; Jeerapan, Itthipon
Abstract : Directly analyzing an herbal drug and its contamination is crucial to avoid severe problems due to uncertain dosages and unwanted contaminants. This article describes the first example of a dosing-spoon-based sensor for point-of-use detection of an herbal extract and its contamination. Andrographis paniculata is an herbal drug conventionally used for the therapy of many symptoms and infectious diseases, including COVID-19. The developed device consists of a sensitive electrochemical sensor, enabling the detection of A. paniculata extract. The lab-on-a-spoon squarewave voltammetric system provides the detection result with favorable sensitivity and simplicity in a short time (less than 15 s). The calibration curve of the modeled herbal extract covers a range of 0.030–7.350 mg ml –1 with a limit of detection of 20 μ g ml –1 . The device and data analysis were applied for determining real samples of A. paniculata extracts. The developed device is sensitive for the screening of processed products from A. paniculata . Moreover, this single dosing-spoon-based sensor can also simultaneously screen the contamination of heavy metals (i.e., cadmium and lead). We envision that this lab-on-a-spoon demonstration would expand the scope of portable pharmaceutical and biochemical sensors, offering promising convenient screening tools for industrial and household applications.